MANAJEMEN PENGELOLAAN WILAYAH PESISIR DALAM MENUNJANG KEPARIWISATAAN DI PANTAI MATTIROTASI KOTA PAREPARE - D, Damis; anti, surianti; anti, Hasrianti; yanti, Fitri (Jurnal Sains dan Teknologi Perikanan, 2022)
Based on the results of research in the management of coastal areas in increasing tourists visiting Mattirotasi Beach, it is known that the results of the analysis of the coastal tourism environment are known to have a coastal height of 0-3 meters above sea level with a slope of 0-8%, coastal bathymetry in the city of Parepare, wind speeds ranging from 173.4 m. /min to 117.6 n/min can generate sea waves with a height of 0.5-1.2 meters. Meanwhile, in the East monsoon, which has a range of wind speeds between 133.2-45 m/s, it is able to generate waves that reach a height of 0.4 – 1.4 meters. up to 0.1852 m/s. With wave intervals ranging from +1.1 meters to 1.5, and seeing the potential for attraction, there is the Nusantara Port which functions as one of the main gates as access to Tanjungpinang City. This area stretches for ± 5 Km and is directly adjacent to the waters, so it has the potential to be developed as a recreational area with the potential to present a sunset view by the beach and Suppa Bay. This condition is also supported by the strategic position of the City of Parepare as a Madya City which is a connecting node in the central part of South Sulawesi Province towards West Sulawesi and the northern part of South Sulawesi Province. Therefore, the Mattirotasi coastal area is a coastal tourist attraction that has quite a variety of attractions. This beach tourism activity is included in the recreational category, which is the type of activity that is most dominantly carried out by tourists.